Faktor-Faktor Yang Mempengaruhi Firm Investment Perusahaan Manufaktur Sektor Industri Barang Konsumsi - Anastassia Budiono, Rousilita Suhendah (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This study was conducted to determine whether the independent variable has a relationship or influence on the dependent variable. The sample in this study was obtained through a non-probability sampling method, having a total of 23 companies in the goods and consumption industry sectors listed on the Indonesia Stock Exchange in 2014 - 2017. The amount of data obtained is 68 data. Data management is carried out using the SPSS program (Statistical Package for Social Sciences) for Windows Version 25. The results of the study show that leverage variables have no negative effect on firm investment, variable liquidity does not have a positive effect on firm investment, and profitability variables have a positive effect on firm investment